If it's not what You are looking for type in the equation solver your own equation and let us solve it.
24=-5w+3(w+6)
We move all terms to the left:
24-(-5w+3(w+6))=0
We calculate terms in parentheses: -(-5w+3(w+6)), so:We get rid of parentheses
-5w+3(w+6)
We multiply parentheses
-5w+3w+18
We add all the numbers together, and all the variables
-2w+18
Back to the equation:
-(-2w+18)
2w-18+24=0
We add all the numbers together, and all the variables
2w+6=0
We move all terms containing w to the left, all other terms to the right
2w=-6
w=-6/2
w=-3
| 7*x+5*(x-1)=-5+12*x | | 9w-3(2w+2)=15 | | -4-9(-8+2n)=-(2n+12) | | 3(8x+14)=2(13x+14) | | 3x^2+134x-4489=0 | | 1624=x+51*26 | | -45-10n=2(6-10n)-7 | | 5y+3=-2y+24 | | 180=3x+4+11+12x | | 5y+3=-2y=24 | | 6/3x=6 | | 8-4t-3(t-5)=2 | | x-5/7=62/3 | | x2=153. | | 5(s−80)=100 | | 4-2(x+2)=x-10 | | 37=5b+7 | | 3a+7-5(a-1)=6 | | 8. -9x+18=6x-72 | | -9=8x=-2(7+4x) | | 1624=400+51*x | | 4-2.x+2=x-10 | | -4(2x-12)(-3x-21)=0 | | 10x+(30-x)25=30*15 | | 2x+4x-26=7+3 | | -31-4k=-10-25k | | 6x-6)+4=-32+6x | | u−407=5 | | 10n+100=400 | | 3.x+1+4=2.x-1 | | x3+2x^2-8x=0 | | 7x+15=5x-3 |